Determinants of a healthy lifestyle and use of preventive screening in Canada - Hopman Wilma M; Phillips Susan P; Qi Vikky (BMC, 2006)
Abstract Background This study explores the associations between individual characteristics such as income and education with health behaviours and utilization of preventive screening. Methods Data from the Canadian National Population Health Survey (NPHS) 1998-9 were used. Independent variables were income, education, age, sex, marital status, body mass index, urban/rural residence and access to a regular physician. Dependent variables included smoking, excessive alcohol use, physical activity, blood pressure checks, mammography in past year and Pap smear in past 3 years. Logistic regression models were developed for each dependent variable. Results 13,756 persons 20 years of age and older completed the health portion of the NPHS. In general, higher levels of income were associated with healthier behaviours, as were higher levels of education, although there were exceptions to both. The results for age and gender also varied depending on the outcome. The presence of a regular medical doctor was associated with increased rates of all preventive screening and reduced rates of smoking. Conclusion These results expand upon previous data suggesting that socioeconomic disparities in healthy behaviours and health promotion continue to exist despite equal access to medical screening within the Canadian healthcare context. Knowledge, resources and the presence of a regular medical doctor are important factors associated with identified differences.